MicroRNAs in the diagnosis of osteoarthritis: a systematic review and meta-analysis of observational studies - Xiaomin Yang; Peng Yin; Xiaoke Yao; Jun Zhang (Journal of Orthopaedic Surgery and Research)
Abstract Background In recent years, the diagnostic and prognostic values of microRNAs (miRNAs) in different diseases have been extensively studied. Therefore, a meta-analysis of miRNAs has been performed to unravel whether miRNAs could be novel diagnostic markers for osteoarthritis (OA). Methods In this meta-analysis, Cochrane, EMBASE, Web of Science, and PubMed were systematically searched for relevant studies on “miRNA” and “OA”. Studies were selected based on pre-defined criteria. Bivariate models were utilized to analyze diagnostic parameters such as summarized diagnostic odds ratio, positive likelihood ratio, negative likelihood ratio, sensitivity, specificity, and area under the summary receiver operating characteristic curve (AUC). Parameters were provided with their corresponding 95% confidence interval (CI). Additionally, the main sources of heterogeneity were probed by conducting subgroup and sensitivity analyses. Results A total of 31 studies from 14 articles were included based on the exclusion and inclusion criteria, encompassing 26 miRNAs and 1842 subjects in total. The pooled estimates unraveled that miRNAs displayed a high diagnostic accuracy, with an overall sensitivity of 0.81 (95% CI, 0.77–0.85) and specificity of 0.85 (95% CI, 0.81–0.88) for diagnosing OA. The overall AUC was 0.90 (95% CI, 0.87–0.92). The subgroup analysis revealed that miRNAs exhibited higher diagnostic efficacy in downregulated genes compared to upregulated genes. miRNAs demonstrated higher diagnostic value in Asian populations than in European populations. Conclusion miRNAs are promising non-invasive biomarkers for the diagnosis of OA with high accuracy. To establish consistency in international diagnostic standards and address the limitations of traditional diagnostic methods, further research is required for validation.